Charterturisme som en produkt: en sociologisk analyse af agens i oplevelsesøkonomien (Sociologisk Forskning, 2011)
Charter tourism as a product: a sociological analysis of agency in the experience economyIn recent years charter tourism as a convenient and cost-effective mode of travelling has been declining. This may be related to dominating societal ideals promoting self-actualization, individual exploration and spontaneity. However, not much is known about the development of ideals and practices among charter tourists. By use of ethnographic fieldwork methodology, including pre-departure and post-travel telephone interviews, this exploratory study investigated a group of Danish charter tourists travelling to Gran Canaria. Results show that the charter tourists were active in navigating between a series of central dilemmas posed by the consumption of a mass product in an individualized societal context, thereby shaping their experiences to form a desirable tourist product.